2013
DOI: 10.1021/nn4044047
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Mechanisms in Escherichia coli Vary for Silver Nanoparticles and Differ from Ionic Silver

Abstract: Silver nanoparticles (Ag NPs) are commonly added to various consumer products and materials to impair bacterial growth. Recent studies suggested that the primary mechanism of antibacterial action of silver nanoparticles is release of silver ion (Ag(+)) and that particle-specific activity of silver nanoparticles is negligible. Here, we used a genome-wide library of Escherichia coli consisting of ∼4000 single gene deletion mutants to elucidate which physiological pathways are involved in how E. coli responds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
376
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(402 citation statements)
references
References 53 publications
21
376
1
4
Order By: Relevance
“…Typically, metal (oxide) NPs will easily dissolve in culture medium (e.g., LB medium) than in (deionized) water. (Ivask et al 2014a;Li et al 2011). However, the toxic tests reveal that the serious toxic damages are normally detected in (deionized) water rather than in culture medium Li et al 2011;Zhang et al 2016) due to the less bioavailable NPs and/ or released metallic ions.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, metal (oxide) NPs will easily dissolve in culture medium (e.g., LB medium) than in (deionized) water. (Ivask et al 2014a;Li et al 2011). However, the toxic tests reveal that the serious toxic damages are normally detected in (deionized) water rather than in culture medium Li et al 2011;Zhang et al 2016) due to the less bioavailable NPs and/ or released metallic ions.…”
Section: Resultsmentioning
confidence: 99%
“…4A) [12]. Recently, Ivask et al [70] used Atomic Force Microscopy to detect Ag NPs at bacterial surface. They showed that positively charged branched polyethylenimine-coated (BPEI) nanoparticles had a much higher affinity toward negatively charged bacteria than commonly used citrate coated (Fig.…”
Section: Role Of the Nanoparticulate Objectsmentioning
confidence: 99%
“…However, selection of in vitro models is often arbitrary, as well as the chosen nanoparticles and exposure conditions. Silver nanoparticles (AgNPs) are interesting for a mechanistic evaluation of in vitro tests because their mechanism of action is suggested to depend on both Ag + and NPs (Ivask et al, 2014;Lemire et al, 2013). In suspension, AgNPs have been described to release ions (Kittler et al, 2010), which strongly contribute to the biological activity of AgNPs in vitro and in vivo (Bouwmeester et al, 2011;Foldbjerg et al, 2012;van der Zande et al, 2012).…”
Section: Introductionmentioning
confidence: 99%